Dampak Pandemi Covid-19 Dan Kreativitas Guru Dalam Pembelajaran Di Indonesia - Muhammad Ayyub Syamsul (Simpati, 2023)
The presence of the Covid-19 pandemic has raised problems in Indonesia's education world. The policy to implement fruitful learning from home is a challenge in carrying out effective learning. An overview of learning in the era of the covid pandemic can be seen from the learning at the end of the 2019/2020 school year from various surveys conducted. The existence of simple online learning and learning that emphasizes giving assignments makes students experience learning boredom. Teacher creativity in carrying out solutive learning is needed through online learning with various complex platforms and offline learning.